Integration of Logistics Mobility and Passengers through Crowdshipping to Reduce Environment Degradation - Purba, Moden; Aimon, Hasdi; Satrianto, Alpon (Journal of Ecohumanism, 2025)
This study intends to examine the chances of combining logistic mobility and aviation passengers using crowdshipping to prevent environmental degradation and analyze four variables: logistic mobility, passengers mobility, and crowdshipping, on environment degradation from 200 aircraft passengers data surveyed and processed using SEM PLS. The results indicate that logistic mobility can significantly increase crowdshipping by 0.381 and environment degradation by 0.998. Passengers mobility can increase Crowshipping by 0.597 and increase Environmental Degradation by 0.338. Crowdshipping can reduce the influence of Environmental Degradation by -0.376. This study successfully highlights the impact and implications of logistics mobility and passenger mobility integration in crowdshipping on environment degradation while opening up new commercial options, through logistics and passenger integration in the cargo transportation business.